Comparing the effectiveness of continuous subcutaneous insulin infusion with multiple daily insulin injection for patients with type 1 diabetes mellitus evaluated by retrospective continuous glucose monitoring: A real-world data analysis - Keyu, Guo; Jiaqi, Li; Liyin, Zhang; Jianan, Ye; Li, Fan; Zhiyi, Ding; Qin, Zhou; Xia, Li; Lin, Yang; Zhiguang, Zhou (Frontiers in Public Health, 2022)
Objective Regarding the effects and practical application of insulin pumps on patients with type 1 diabetes mellitus (T1DM), the real-world evidence is limited especially concerning the incidence of hypoglycemia. This study aimed to compare the efficacy of continuous subcutaneous insulin infusion (CSII) therapy with multiple daily injection (MDI) therapy on glycemic metrics evaluated by retrospective continuous glucose monitoring (CGM) in Chinese patients with T1DM. Methods In total, 362 T1DM Chinese patients from the outpatient department of the Second Xiangya Hospital, Central South University, who underwent intensive insulin therapy and used a retrospective CGM system were included in this retrospective cross-sectional study. Comprehensive analysis of clinical and biological features and retrospective CGM derived-metrics was performed on the 362 enrolled T1DM patients who underwent CSII (n = 61) or MDI (n = 301) therapy (defined as 4 or more insulin injections per day). Results Our findings demonstrated that patients who underwent CSII therapy, compared with those who received MDI therapy, had lower levels of hemoglobin A1c (HbA1c) and fasting blood glucose; moreover, CSII therapy was associated with better glycemic outcomes in terms of increasing time in range (TIR), decreasing time above range (TAR), and achieving CGM-associated targets of TIR ≥70% and TAR <25%. However, patients who underwent CSII therapy did not experience decreasing time below range (TBR), achieving CGM-associated targets of TBR <4%, and reduction of the risk of hypoglycemia as evidenced by comparing TBR and low blood glucose index (LBGI) between the two treatment regimens. The parameters of glycemic variability, such as standard deviation of glucose (SD), mean amplitude glycemic excursion (MAGE), and large amplitude glycemic excursion (LAGE) in T1DM patients who underwent CSII therapy outperformed. Conclusion Our results provided further evidence that CSII therapy is safe and effective for management of Chinese T1DM patients, which was confirmed by a lower HbA1c level and better CGM-derived metrics but no demonstration of improvment in the risk of hypoglycemia. To achieve more satisfactory glycemic outcomes through the utilization of CSII therapy for Chinese T1DM patients, a strong physician-patient relationship is essential.